INFLUENCE OF INTERSECTION ON WALKABILITY INDEX IN CAMPUS AND SURROUNDINGS (CASE STUDY INDONESIA AND JAPAN) - Ulman Idris, Muhammad Ikram (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
As one of the nations with biggest number of populations, Indonesia should concern the best practice and way to design their cities, including the urban form. City complexity to provide high amounts of activities could be determined by how the road, streets, and path were designed in terms of the form and directions. Some assessments have been developed to examine the effectiveness of the streets and paths for the pedestrian. University campus, which sometimes recognized as miniature of the city were chosen as the case of this study, and will try to find the correlation between walkability index and number of intersections in Indonesian campus and compared with Japanese Campus as a benchmark. This study will try to revealed if the number of intersections have impact to the walkability value in Indonesia’s and Japan’s universities and its surrounding areas by using several methods such as measuring the walkability value from author’s previous research and combine it with connectivity formula. Walkability and connectivity maps are produced with some graphics to showing the relationship of those main topic.